The Influence of Digital Leadership on Employee Performance with Digital Culture as A Moderating Variable - Nugroho, Heru; Riyadi, Selamet; Mudjijah, Slamet; Maulana, Panca; Safitra, Ravindra (Maneggio, 2024)
This study examines the influence of digital leadership on employee performance with digital culture as a moderating variable. In today’s rapidly evolving digital landscape, organizations require leaders who can navigate technological changes and foster a culture that supports innovation and collaboration. The primary aim of this research is to assess how digital leadership impacts employee performance and to explore the role of digital culture in enhancing this relationship. Using a quantitative research method, a survey was conducted with 200 respondents from various industries. Data were analyzed using multiple regression analysis to evaluate the relationships between digital leadership, digital culture, and employee performance. The findings reveal that digital leadership has a significant positive effect on employee performance, and that digital culture moderates this relationship by enhancing the effects of leadership on performance. These results highlight the importance of both digital leadership and digital culture in improving organizational performance in the digital era.